SISTEM ADMINISTRASI PPh PASAL 21 PEGAWAI DINAS LINGKUNGAN HIDUP KOTA MEDAN - Fikhri Haikal; Deby Siska Oktavia Pasaribu; Roni Juliansyah (MTU PRESS, 2025)
This final assignment will be carried out at the Medan City Environmental Service starting from April 10 2023 to June 8 2023. This final assignment aims to find out the Article 21 income tax (PPh) administration system for Medan City Environmental Service employees. Income Tax Article 21 is a tax imposed on income obtained by individual taxpayers. The income referred to here is income in the form of compensation or compensation relating to work or services received or obtained including salary, wages, allowances, honorarium, commission. , bonuses, gratuities, pensions, or other forms of compensation, income tax article 21 cannot be separated from the administrative system. Meanwhile, the benefit of this research is as information material for parties who need it and as a reference for future researchers. The data method used is the descriptive method. Data collection was carried out by means of observation and documentation. Based on research conducted, the income tax administration system for Article 21 employees of the Medan City Environmental Service is effective in terms of following government regulations and other rules governing Income Tax Article 21.